2014
DOI: 10.1136/tobaccocontrol-2014-051763
|View full text |Cite
|
Sign up to set email alerts
|

Air quality in New York City hookah bars

Abstract: Background Hookahs (e.g., water pipes) are increasingly being used in the U.S. and elsewhere. Despite the popularity of hookah bars, there is a paucity of research assessing the health effects of hookah smoke, and although New York City (NYC) bans indoor tobacco smoking, hookah lounges claim that they only use herbal products without tobacco and are exempt. This study investigated levels of multiple indices of air pollution in the indoor air of hookah bars in NYC. Methods Air samples were collected in 8 hook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 43 publications
7
35
4
Order By: Relevance
“…Interestingly, air quality levels in the smoking rooms and adjacent rooms in hookah-smoking homes were found to be similar with those of hookah bars with multiple smokers and little to no ventilation 25 30…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Interestingly, air quality levels in the smoking rooms and adjacent rooms in hookah-smoking homes were found to be similar with those of hookah bars with multiple smokers and little to no ventilation 25 30…”
Section: Discussionmentioning
confidence: 86%
“…CO poisoning after hookah smoking has already been found in a number of case reports, with users presenting carboxyhaemoglobin levels 34% higher than normal after hookah use,43 44 syncope45 and confusion 46. It has been suggested that CO intoxication due to hookah smoking is likely to be more common than that was realised due to inefficient charcoal burning 30 47. These findings suggest that the substitution of the burning charcoal with an electronic heating source may be beneficial in reducing CO levels during the use of hookahs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Even in municipalities in which cigarette smoking in cafes, bars, and restaurants has been banned, regulatory loopholes have resulted in a flourishing trend of waterpipe smoking in such venues, e.g., Baltimore, MD, and New York City, NY, USA, where investigators have recently measured unacceptably high levels of PM 2.5 , carbon monoxide (CO), and other pollutants released from waterpipes. 23,24 …”
Section: Discussionmentioning
confidence: 99%